Jesus Christ, a compassionate companion: Christological reflections in the time of the HIV/AIDS pandemic - E. S. Mligo (Acta Theologica)
Who do people living with HIV/AIDS say Jesus Christ is in their context of stigmatisation? This is an ancient Christological question that helps us understand and deal with this issue in a new way. This article presents the views of people living with HIV/AIDS about the role of Jesus to them in a context of HIV/AIDS-related stigmatisation. Through their reading of biblical texts from the Gospel according to John, people living with HIV/AIDS argue that Jesus Christ is a compassionate companion who not only sympathises with them, but also cares for them and seeks to improve their situation. In this instance, the article critiques the “cult of normalcy” ever embraced by the church that excludes those it considers to be abnormal and includes those it considers to be normal. This “cult of  normalcy” is contrary to the compassionate way in which Jesus treated those who were suffering.